2017
DOI: 10.5539/jmr.v9n4p101
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for the Vector Transmission and Control of Banana Xanthomonas Wilt

Abstract: Banana Xanthomonas wilt is currently wrecking havoc in East and Central Africa. In this paper, a novel theoretical model for the transmission of banana Xanthomonas wilt by insect vectors is formulated and analyzed. The model incorporates roguing of infected plants and replanting using healthy suckers. The model is analyzed for the existence and stability of the equilibrium points. The global stability of the disease-free equilibrium point was determined by using a Lyapunov function and LaSalle's invariance pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Several mathematical models have been derived by researchers to understand the transmission dynamics of BXW disease and provide possible control techniques. In [9], the authors derived a model to understand the transmission structure of the BXW epidemic by vectors with control measures. In [10], the authors proposed a non-linear model to analyze the role of contaminated measures in the reiteration of BXW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mathematical models have been derived by researchers to understand the transmission dynamics of BXW disease and provide possible control techniques. In [9], the authors derived a model to understand the transmission structure of the BXW epidemic by vectors with control measures. In [10], the authors proposed a non-linear model to analyze the role of contaminated measures in the reiteration of BXW.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the aforementioned studies of mathematical modeling of the BXW disease [9][10][11][12][13][14] have yet to be analyzed using fractional derivatives. In this paper, we generalize the non-linear control-based model of BXW [14] by using Caputo fractional derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the dynamics of BXW disease, several scholars have developed mathematical models to study the transmission dynamics of BXW and its controls. Horub et al [24] developed a mathematical model to study the transmission dynamics of BXW disease by vectors and its controls. The study showed that timely removing the male bud using a forked stick, increasing rougeing and planting health suckers helps to reduce transmission of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, whitefly vector is considered to be the cause. Banana Xanthomonas wilt deterministic model also proposed by Horub and Julius (2017). This model was formulated and analyzed with system of ordinary differential equation.…”
Section: Introductionmentioning
confidence: 99%